A Review of Process Parameters and Morphology of HTS YBCO by Electrospinning Technique - Saleh, Eesaa Jasim; Mohamad Ashry, Jusoh; Muhammad, Hafiz; Rajan, Jose (Universiti Malaysia Pahang, 2016)
Various homogeneous aqueous solutions of high-temperature superconductor YBa2Cu3O7-δ (HTS YBCO) have been prepared successfully during the last years. These HTS YBCO were synthesized using sol-gel accompanied with an electrospinning technique using plenty polymers and having varieties of concentration ratio. The polymeric solution and amorphous precursor were used to create an atomic level interaction between different salts to prepare HTS YBCO. This review focuses on the basic parameters utilizing in electrospinning process and their effects on the diameter morphologies of HTS YBCO nanostructures. The results showed that increasing applied voltage, polymer concentration ratio in the precursor solution, flow rate injection, viscosity, and the jet or needle diameter systematically enhanced the diameter of the nanostructure.